First Report of Endolithic Members of Rhodosorus marinus (Stylonematales, Rhodophyta) Growing Inside Rhodoliths Offshore Louisiana, Northwestern Gulf of Mexico - Krayesky-Self, Sherry; Phung, Delena; Schmidt, William; Sauvage, Thomas; Butler, Luke; Fredericq, Suzanne (Frontiers in Marine Science, 2020)
Endolithic, red unicells residing in the interior of Lithothamnion rhodoliths, collected offshore the NW Gulf of Mexico in mesophotic rhodolith beds at ~54-55 m depth and maintained in closed microcosms, were used to establish cultures following their isolation. These endolithic unicells subsequently developed into amorphous blobs of palmelloid cell colonies. Each cell contains unstacked, 2-5 lobed parietal chloroplasts, one prominent central pyrenoid, and have a thin or thick cell wall. Single cells, or cell clusters (in pairs, tetrads, or up to 12) are embedded inside an extracellular matrix whose boundaries remain closely appressed to neighboring cell clusters. Cell division by concavo-convex division resulted in hemispherical cells subsequently expanding in size. Plastid tufA, psbA and 16S rDNA sequence analyses confirmed that the colonies are Rhodosorus marinus Geitler. This is the first report of a red alga spending part of its life history endolithically inside biogenic rhodoliths.